Raised bed plantingA proven technology under climate change scenario - Sahu, Raghubar; Sohane, R K; Kumar, Rakesh (Indian Farming, 2024)
In the Indo-Gangetic Plains (IGP) of South Asia, the chance of crop loss increases when heavy monsoon rains create floods and water logging conditions under flat sowing. Crops in semi-arid and arid areas do not need to be irrigated as much when they are grown on a permanent raised bed, which also lessens the negative effects of excess water on crop output. Crops are grown on raised beds using the crop establishment technique known as bed planting. The bed planter includes movable blades that may be used to create raised beds of various widths and heights by moving the blades on the frame and the roller on the back. The multi crop bed planter, which has an inclined seed metering mechanism, is used to sow seeds into raised beds. Prior to planting each succeeding crop, permanent raised beds with little reshaping of the furrows between the raised beds are required to save cultivation costs and improve system sustainability. Additionally, it regulates the movement of machines, restricting compaction to the furrow bottoms, enabling the use of lower seeding rates than with conventional planting techniques, and minimizing crop lodging.